Terang Dunia di Ruang Peradilan: Rekonstruksi Etika Teologis-Hukum dalam Pembelaan Tersangka Korupsi Berdasarkan Matius 5:14–15 - Rully Simorangkir (JURNAL LUXNOS, 2026)
This article examines the ethical dilemma faced by Christian lawyers who defend corruption suspects by using Matthew 5:14–15 as the main theological foundation. The central issue is not whether corruption suspects may be defended, since legal assistance and the presumption of innocence belong to the rule of law. The more decisive question is how such defense should be conducted without becoming a justification for corruption, a manipulation of facts, or an obstruction of justice. Using a normative-interdisciplinary method, this article combines historical-grammatical and constructive exegesis of Matthew 5:14–15 with normative legal analysis. It argues that the metaphors of “the light of the world,” “a city on a hill,” and “a lamp on a stand” provide a public-identity framework for Christian discipleship that is relevant to legal practice. The novelty of this article lies in the model of “light of the world in the courtroom,” a theological-legal ethical framework that positions Christian lawyers as defenders of legal rights and public witnesses to truth and justice.